Metavirome Analysis of Culex tritaeniorhynchus Reveals Novel Japanese Encephalitis Virus and Chikungunya Virus - Zhang, Duo; Peng, Chengcheng; Li, Chenghui; Li, Yiquan; Zhang, He; Li, Nan; Xiao, Pengpeng (Frontiers in Cellular and Infection Microbiology, 2022)
To explore the Culex Tritaeniorhynchuses-specific virome, 6400 Culex Tritaeniorhynchuses were collected in Honghe autonomous prefecture, China. Abundant virus sequences were obtained from 28 viral families using metavirome sequencing. Herein, several viruses in Culex Tritaeniorhynchuses virome were verified using PCR technique, which covering Japanese encephalitis virus (JEV), Getah virus (GETV), and even Chikungunya virus (CHIKV). Seven JEV gene sequences were amplified successfully, of which JEV-China/CT2016E-1 shared the highest homology with the known JEV sequence isolated in Korea,1946, with at least 96.1% nucleotide (nt) identity, which belonged to genotype III. Nine CHIKV gene sequences were amplified, which shared the highest with at least 93.0% nt identity with CHIKV from Thailand isolated in 2007, which was assigned to genotype Asian. Remarkably, CHIKV was isolated from Culex tritaeniorhynchus in China for the first time. It was initially confirmed that the isolated virus CHIKV-China/CT2016-1 may increase infectivity after passaged in Vero cells from BHK-21 cells. Collectively, our study reveals the diversity, properties, and potential virus susceptibility dynamics of Culex tritaeniorhynchus virome, and sheds new perspectives on the viral ecology in other important biological vectors.